Error Analysis of Generating Compound Sentence on Indonesian EFL Students - Agustina Ramadhianti (STKIP PGRI Tulungagung, 2024)
Compound sentence is one of sentence types that need to be paid attention to using appropriate conjunction in combining ideas. For some students, this type is not always easy to construct the combination in the structure and ideas. This study aims at analyzing the students’ error in writing compound sentence. The research applied the descriptive qualitative research, by using the purposive sampling. The research engaged 60 students of Writing Class at English Education Program in University of Indraprasta PGRI. The data collection was taken from the students’ writing of compound sentence task, and it analyzed and classified into some sentence error based on Hacker and Sommers (2011). The finding shows the most common error that students made in constructing compound sentence is run-on sentence with 63.3% from total errors. By knowing this finding, hopefully the lecturers encourage the students in generating good compound sentence, and recurrently denote some errors examples of compound sentence.